2021
DOI: 10.1371/journal.pone.0259005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterisation of carbapenemase encoding genes in multidrug-resistant Gram-negative bacilli

Abstract: Background Emerging worldwide in the past decade, there has been a significant increase in multidrug-resistant bacteria from serious nosocomial infections, especially carbapenemase-producing Gram-negative bacilli that have emerged worldwide. The objective of this study is to investigate carbapenem resistance in Gram-negative bacilli bacteria using phenotypic detection, antimicrobial resistance profiles and genotypic characterisation methods. Methods 200 Gram-negative bacilli isolates were collected from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
9
16
1
1
Order By: Relevance
“…To decrease the threat of infection spreading in the hospital and to reduce mortality rates, this study re-connoitered the existence of carbapenemase-producing organisms using phenotypic methods and determined the distribution of carbapenemase genes by genotypic testing. The prevalence of carbapenem resistance was 17.0% in this study, which is similar to Haji et al 18 ’s study. The incidence of prevalence in various parts of India varies from 14-69%.…”
Section: Discussionsupporting
confidence: 91%
“…To decrease the threat of infection spreading in the hospital and to reduce mortality rates, this study re-connoitered the existence of carbapenemase-producing organisms using phenotypic methods and determined the distribution of carbapenemase genes by genotypic testing. The prevalence of carbapenem resistance was 17.0% in this study, which is similar to Haji et al 18 ’s study. The incidence of prevalence in various parts of India varies from 14-69%.…”
Section: Discussionsupporting
confidence: 91%
“…Genes encoding class A carbapenemases, like blaKPC, have also not been found in any of our isolates. These findings were consistent with previous research in Kufa-Iraq (Tuwaij, 2016) and Baghdad (Ghaima, 2018), but disagreed with a study in Erbil (Haji et al, 2021) that recorded KPC in its isolates. This is likely the first report of carbapenemase genes in clinical isolates of A. baumannii in Duhok province, Iraq.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies revealed that K. pneumoniae and A. baumannii harbored more than one gene, making them more likely to be multi-or pan-drug resistant. [49][50][51][52][53] This finding can be challenged due to risk of resistance transmission and restricted antibiotics valuable for…”
mentioning
confidence: 99%
“…However, Haji et al reported only two isolates that do not show any genes. 52 The efficacy of MAST-Carba plus in detection of carbapenemase activity was evaluated in relation to PCR results. The highest sensitivity, specificity, positive and negative predictive values was reported for OXA-48 detection (81.8% 92.5%, 75% and 94.9, respectively).…”
mentioning
confidence: 99%